2014
DOI: 10.5301/jbm.5000080
|View full text |Cite
|
Sign up to set email alerts
|

Serum ANGPTL2 Levels Reflect Clinical Features of Breast Cancer Patients: Implications for the Pathogenesis of Breast Cancer Metastasis

Abstract: These findings suggest that serum ANGPTL2 levels in breast cancer patients could represent a potential marker of breast cancer metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 20 publications
1
38
0
Order By: Relevance
“…Another interesting feature of our study was the existence of a statistically significant correlation between ANGPTL2 expression in primary lesions and the levels of ANGPTL2 in serum. Recently, Endo and colleagues demonstrated that breast cancer cells secrete ANGPTL2 in vitro and in vivo, and serum ANGPTL2 levels in patients with metastatic breast cancer were significantly higher compared with healthy controls (27). This report supports our hypothesis that serum ANGPTL2 in patients with colorectal cancer is likely secreted by primary colorectal cancer tissues.…”
Section: Discussionsupporting
confidence: 80%
“…Another interesting feature of our study was the existence of a statistically significant correlation between ANGPTL2 expression in primary lesions and the levels of ANGPTL2 in serum. Recently, Endo and colleagues demonstrated that breast cancer cells secrete ANGPTL2 in vitro and in vivo, and serum ANGPTL2 levels in patients with metastatic breast cancer were significantly higher compared with healthy controls (27). This report supports our hypothesis that serum ANGPTL2 in patients with colorectal cancer is likely secreted by primary colorectal cancer tissues.…”
Section: Discussionsupporting
confidence: 80%
“…Figure 3B). More recently, it was reported that serum ANGPTL2 levels in patients with metastatic breast cancer are significantly higher than those in healthy individuals or in patients with ductal carcinoma in situ or non-metastatic invasive ductal carcinoma [48]. This finding raises a possibility that serum ANGPTL2 levels in breast cancer patients could be a potential marker of breast cancer metastasis.…”
Section: Roles Of Angptl2 In Carcinogenesis and Metastasismentioning
confidence: 98%
“…In vitro studies performed in skin squamous and HCC lines, as well as in lung and osteosarcoma cell lines, further support these findings (147,148,150,151). Interestingly, ANGPTL2 levels may represent a potential biomarker in various tumour types, such as breast (152) or oesophageal cancer (153). On the other hand, ANGPTL2 has been found to inhibit ovarian cancer cell growth in vitro (154).…”
Section: Angiopoietin-like Proteinmentioning
confidence: 65%